Prenatal Diagnosis and Fetal Outcomes of Cystic Hygroma: Experience of a Tertiary Hospital - Yakistiran, Betul; Katlan, Doruk Cevdi; Yuce, Tuncay; Soylemez, Feride (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Cystic hygromas of nuchal origin are reported to be associated with fetal aneuploidy and structural anomalies in 50-80% of the cases. We aimed to report our experience on cystic hygromas via 18 cases. Study Design: We conducted a retrospective study based on a review of medical records of patients who had fetal septated cystic hygroma, diagnosed by ultrasonography, in the Ankara University School of Medicine, Department of Obstetrics and Gynecology, between 2012 and 2016. All patients were provided with genetic counselling and prenatal invasive diagnostic procedures were applied to obtain fetal karyotype. Results: We observed 18 cases of fetal cystic hygroma among these patients (0.39%). The abnormal karyotypes were: Turner syndrome (45X0) in 3 (16.7%), trisomy 21 in 2 (11.1%), trisomy 18 in 1 (5.6%) and mosaic Turner syndrome in 1 (5.6%) patient. Conclusion: The presence of cystic hygroma carries a high risk for aneuploidy and major structural malformations. Invasive prenatal diagnostic procedures for fetal karyotype analyses and parental counselling about poor perinatal prognosis is mandatory.